Análise de dados administrativos de e-commerce: Uma abordagem focada no cliente - Carvalho, Brayner Cristian Mello; Lazarin, Nilson M. (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.233492, 2023)
With the increase of e-commerce, the most diverse virtual scams were created and spread throughout the Internet. Furthermore, deciding whether a store is safe for online shopping is not always easy. Then, the user must have tools at his disposal to verify the legitimacy of the e-commerce. Therefore, this work presents an approach to identify administrative data on e-commerce sites with Top-Level Domains “.BR”. Besides, a browser extension was developed that crosses the legal entity data with the domain registration. With this, this paper aims to contribute to users’ decisions about e-commerce.